EFFECT OF Crotalus durissus terrificus (LAURENTI, 1768) VENOM ON THE EVOLUTION OF EHRLICH ASCITES TUMOR - Silva, R. J. Da [UNESP]; Fecchio, D.; Barraviera, B. [UNESP] (Centro de Estudos de Venenos e Animais Peçonhentos - CEVAP, Universidade Estadual Paulista - UNESP, 1997)
The effect of Crotalus durissus terrificus (LAURENTI, 1768) venom on the evolution of Ehrlich ascites tumor cells was evaluated. Thus, 30-day-old male mice of the Swiss strain were inoculated intraperitoneally with 1x10 tumor cells. Then, 7 groups of animals were formed: 3 control groups (physiological, venom and tumor) and 4 experimental groups that received different doses of venom. The experimental groups received 5 intraperitoneal venom injections on the 1 , 4 , 7 , 10 and 13 days after tumor implantation. On the 14 day, 5 animals from each one of the groups were sacrificed, and the variables such as the total and differential counts of cells in the peritoneal cavity and functional state of peritoneal macrophages by macrophage spreading were evaluated. The other 5 remaining animals were kept in the laboratory for 60 days for observation of their survival percentage. The results obtained were statistically analyzed by the Kruskal-Wallis test at 5% significance level. It was observed that Crotalus durissus terrificus venom increases survival time of mice, but does not increase mortality percentage. This venom also increases the percentage of macrophage spreading. We suggest that snake venoms can cause inhibition of tumor growth by activating the inflammatory reaction, mainly the macrophages, stimulating the production of TNF- , IL-1, IL-6 and IL-8. These cytokines may act on tumor cells by different mechanisms, inducing its complete elimination.
Keywords: venom; inflammation; tumor growth; Crotalus durissus terrificus